General plan and phases of implementation of the BIM concept in the construction industry - Tugay, A.A.; Pokolenko, V.O.; Yesipenko, A.D.; Dubinka, A.V. (Ways to Improve Construction Efficiency, 2021)
Building Information Modeling (from English, Building Information Modeling, BIM) – the use of a general digital representation of an object under construction to facilitate the design, construction and operation processes in order to create a reliable basis for decision making. The Building Information Model (from English, Building Information Models, BIMs) is a set of structured and unstructured information containers (datasets) within a holistic information system, containing the necessary geometric, physical, functional and other characteristics of an object, which are a source for documentation accompanying the life cycle of an object (project documentation, estimates, etc.). The content of the construction information model is identical to the content of the project documentation, expanded with additional data. Within the construction industry, it is the implementation of specific tasks and procedures applied to the processes of entering, processing, creating and transmitting data to ensure the accuracy and integrity of information throughout the entire life cycle of an object, based on the definition of Information Management. This is to guide the implementation of BIM in an organization, ensure that BIM-related goals are achieved, and support the development / delivery of new services and the effectiveness of information modeling. The implementation and development of ВIM technologies requires the creation of communities that will serve as a tool for the promotion and implementation of ВIM technologies. In Ukraine, there is no expert environment on ВIM at the state level, but it is available in business. Therefore, the logical formula for creating a common platform for the promotion of VIM would be to involve representatives of all stakeholders with equal voting rights: the state, business, the public. It is proposed to create a community of UA BIM Task Group for the period necessary for sufficient integration of ВIM into the construction industry (approximately 10-15 years). The organization should consist of three components: membership; expert; secretariat.